2018
DOI: 10.1002/ajh.25102
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular toxicity in patients with chronic myeloid leukemia treated with second‐generation tyrosine kinase inhibitors in the real‐life practice: Identification of risk factors and the role of prophylaxis

Abstract: Long-term treatment with the second-generation tyrosine kinase inhibitors (2 ndG TKIs) nilotinib and dasatinib may result in cardiovascular (CV) complications. Accumulating evidence suggests that the combination of a median age at the time of chronic myeloid leukemia (CML) diagnosis of greater than 60 years, when CV adverse events (AEs) are common, and the CV toxicity of 2 ndG TKIs represents per se a potential predisposing factor, which requires preventive strategies and CV surveillance in patients with CM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 7 publications
3
16
0
Order By: Relevance
“…AOEs represent off‐target relevant complications of TKIs, particularly second‐generation and third‐generation TKIs . Nilotinib and ponatinib interact with a considerable number of clinically relevant vascular targets implicated in endothelial cell survival and angiogenesis …”
Section: Discussionmentioning
confidence: 99%
“…AOEs represent off‐target relevant complications of TKIs, particularly second‐generation and third‐generation TKIs . Nilotinib and ponatinib interact with a considerable number of clinically relevant vascular targets implicated in endothelial cell survival and angiogenesis …”
Section: Discussionmentioning
confidence: 99%
“…In the prospective study by Caocci et al in 369 CML adult patients with the median age 50 years and median follow-up 4 years, who were stratifi ed according to the SCORE system, the patients with TCH > 5.17 mmol/l and LDL-CH > 1.8 mmol/l 3 months after treatment had a signifi cantly higher incidence of CVEs and high or very high SCORE risk maintained a signifi cant association with CVEs (25). The authors concluded that SCORE risk seemed to be useful to predict the development of atherosclerotic events in CML patients treated with nilotinib and should be calculated before the start of any TKIs (27).…”
Section: Discussionmentioning
confidence: 99%
“…The 10-year cardiovascular risk of CML patients can be assessed using the Systematic Coronary Risk Evaluation (SCORE) chart, Framingham score, or QRisk ® 3–2018 algorithm; thus, the precondition of atherosclerotic risk events in patients, before and during treatment with TKIs, should be evaluated [ 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%